How does HIV testing modality impact the cascade of care among persons diagnosed with HIV in Ethiopia? - Malin Johansson; Clara Penno; Niclas Winqvist; Fregenet Tesfaye; Per Björkman (Taylor & Francis Group, 2021)
Background Despite scaling up of HIV programmes in sub-Saharan Africa, many people living with HIV (PLHIV) are unaware of their HIV status. New testing modalities, such as community-based testing, can improve test uptake, but it is uncertain whether type of testing modality affects the subsequent cascade of HIV care. Objective To compare linkage to care and antiretroviral treatment (ART) outcomes with regard to type of HIV testing modality. Methods A retrospective registry-based study was conducted at public ART clinics in an urban uptake area in Central Ethiopia. Persons aged ≥15 years newly diagnosed with HIV in 2015-2018 were eligible for inclusion. Data on patient characteristics and testing modality were analysed for associations with the following outcomes: ART initiation, retention in care at 12 months after starting ART, and viral suppression (<1000 copies/ml, recorded during the first 12 months after ART initiation), using uni- and multivariable analysis. Separate analyses disaggregated by sex were performed. Results Among 2885 included PLHIV (median age 32 years, 59% female), 2476 (86%) started ART, 1422/2043 (70%) were retained in care, and 953/1046 (92%) achieved viral suppression. Rates of ART initiation were lower among persons diagnosed through community-based testing (adjusted odds ratio [AOR] 0.44, 95% confidence interval [CI] 0.29-0.66) and among persons diagnosed through provider-initiated testing (AOR 0.65, 95% CI 0.44-0.97) compared with facility-based voluntary counselling and testing. In sex-disaggregated analyses, community-based testing was associated with lower rates of ART initiation among both women and men (AOR 0.47, 95% CI 0.27-0.82; AOR 0.39, 95% CI 0.19-0.78, respectively). No differences were found for retention in care or viral suppression with regard to test modality. Conclusion Type of HIV testing modality was associated with likelihood of ART initiation, but not with subsequent treatment outcomes among persons starting ART.